060 Soccer players who rupture their ACL demonstrate biomechanical risk factors while decelerating: a prospective cohort study. (3rd March 2020) - Dix, Celeste; Arundale, Amelia; Silvers-Granelli, Holly; Zarzycki, Ryan; Marmon, Adam; Snyder-Mackler, Lynn
Abstract : Background: Many non-contact anterior cruciate ligament (ACL) injuries amongst women's soccer players occur during a deceleration manoeuvre. Retrospective video analysis of ACL injuries has demonstrated that players are often in knee valgus at the time of injury. Whether the components of valgus collapse: hip adduction, hip internal rotation, and knee abduction angles during a deceleration task, differ between players who go on to ACL injury has not been prospectively examined. In order to develop more effective injury prevention programs, it is necessary to understand these risk factors in the context of a sport-specific task. Objective: To compare whether hip and knee kinematics during a deceleration differ between collegiate women's soccer players who go on to sustain ACL injury and those who don't. Design: Prospective cohort non-randomized intervention study. Setting: Collegiate women's soccer. Patients (or Participants): 51 collegiate women's soccer players. Interventions (or assessment of risk factors): Preseason, three-dimensional motion analysis of a deceleration. Main outcome measurements: Descriptive statistics for injured limbs and the mean of uninjured players' limbs were calculated for peak values of valgus collapse components (hip adduction, hip internal rotation, knee abduction). A MANOVA was also used to determine whether there were biomechanical differences between Injured (N=4) and Uninjured (N=47) players. Results: There was a significant difference between groups for hip adduction angle (p=0.03). The Injured players were in much more hip adduction (8.63±4.1°) than those who remained Uninjured (1.66±6.0°). There were no other significant or clinically meaningful differences between groups for hip internal rotation or knee abduction angle. Conclusions: Hip adduction during deceleration differed between players who went on to ACL injury and those who did not. Therefore, the components of knee injury prevention programs that address lateral and posterior hip strength and neuromuscular control are likely crucial components of ACL injury prevention programing for soccer players.